2021
DOI: 10.3390/su13179857
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Conservation Agriculture to Soil Security

Abstract: Soil securitization is increasingly becoming a quintessential currency for attaining sustainable development given the mounting global concerns of land degradation, loss of biological diversity and associated ecosystem services, climate change, food insecurity, and water stress. A well-functioning soil is a panacea to address these global concerns. This paper describes the contribution of conservation agriculture (CA) to biological diversity protection, climate change adaptation and mitigation, ecosystem servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…Conversion of plow tillage to a system-based CA can restore soil health by reducing losses of SOC and improving use efficiency of inputs, thereby advancing the mission of COP28. Adoption of CA has been documented to improve biodiversity, adaptation and mitigation of climate change, delivery of ESs, enhancement of FNS, and increase of water security, while serving as an entry point for improving soil health and its securitization (Mugandani et al 2021;Lal 2015). The global land area under CA is estimated at 205 million ha (~506 million ac) (Kassam et al 2022), and there is a vast scope for upscaling the global adoption of CA leading to conservation and restoration of soil health.…”
Section: Agronomic Practices For Enhanc-ing Soil Health and Advancing...mentioning
confidence: 99%
“…Conversion of plow tillage to a system-based CA can restore soil health by reducing losses of SOC and improving use efficiency of inputs, thereby advancing the mission of COP28. Adoption of CA has been documented to improve biodiversity, adaptation and mitigation of climate change, delivery of ESs, enhancement of FNS, and increase of water security, while serving as an entry point for improving soil health and its securitization (Mugandani et al 2021;Lal 2015). The global land area under CA is estimated at 205 million ha (~506 million ac) (Kassam et al 2022), and there is a vast scope for upscaling the global adoption of CA leading to conservation and restoration of soil health.…”
Section: Agronomic Practices For Enhanc-ing Soil Health and Advancing...mentioning
confidence: 99%
“…Given that in times of drought, even natural water reserve is limited, by principles of sustainable agriculture, it is necessary to use early warning systems for droughts and apply effective management [21,22,23,24]. Due to increasing water requirements for crops, efficient management of water resources in agriculture means efficient use of irrigation water, conservation of soil water supply, and reduction of energy consumption for irrigation [25,26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the benefits of CA practices compared to tillage-based conventional agriculture in enabling sustainable improvement of soil productivity [16], [17] [18]. The practice of CA can increase the organic matter content in soil [19], and enhance soil biological activity [20] [21], which helps to improve soil structure and crop yields after several years of practice [22]. For [21], conservation agriculture, which enhances soil biodiversity, is a departure from agricultural intensification.…”
Section: Introductionmentioning
confidence: 99%
“…The practice of CA can increase the organic matter content in soil [19], and enhance soil biological activity [20] [21], which helps to improve soil structure and crop yields after several years of practice [22]. For [21], conservation agriculture, which enhances soil biodiversity, is a departure from agricultural intensification.…”
Section: Introductionmentioning
confidence: 99%